Comparison of the Cc and R3c space groups for the superlattice phase of Pb(Zr 0.52Ti 0.48)O 3 - Ranjan, R.; Singh, A.K.; Ragini; Pandey, D. (My University, 2005)
Recent controversy about the space group of the low temperature superlattice phase of Pb(Zr 0.52Ti 0.48)O 3 is settled. It is shown that the R3c space group for the superlattice phase cannot correctly account for the peak positions of the superlattice reflections present in the neutron diffraction patterns. The correct space group is reconfirmed to be Cc. A comparison of the atomic coordinates of Cc and Cm space groups is also presented to show that in the absence of superlattice reflections, as is the case with x-ray diffraction data, one would land up in the Cm space group. This superlattice phase is found to coexist with another monoclinic phase of the Cm space group.
Keywords: superlattice; Pb(Zr 0.52Ti 0.48)O 3; neutron diffraction patterns